DETERMINAN TINGKAT KEMISKINAN DI KOTA BANDUNG - Kharisma, Bayu; Santoso, Teguh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to find the determinants of household poverty status in the city of Bandung by using the National Socioeconomic Survey (Susenas) of March 2018 Expenditure Consumption in Bandung. The methodology used is an ordered logit regression model. The results showed that the demographic characteristics variables that had a significant and positive effect on the poverty status of households in the city of Bandung were female household heads, marital head households and household size and dependency burden. Meanwhile, economic characteristics, namely household access to the internet, ownership of mobile phones (HP), ownership of one's own residence, and access to business credit have a negative and significant effect on household poverty status in the city of Bandung. Furthermore, social characteristics that negatively affect the status of household poverty in the city of Bandung are variable levels of school education as measured by the years of schooling.